Case report and literature review: Giant retroperitoneal cystic lymphangioma - Su, Tieshan; Li, Chaoyuan; Song, Bin; Song, Defeng; Feng, Ye (Frontiers in Surgery, 2023)
Background Cystic lymphangioma is a rare benign tumor of the lymphatic system, which is most commonly observed in the neck, head and armpit.Less than 5% of lymphangiomas occur in the abdominal cavity and even less in the retroperitoneum. Case description A 65-year-old male patient was diagnosed with an “abdominal mass that had persisted for 1 year, accompanied by abdominal pain, abdominal distension and dyspnea for 7 days”. After abdominal computerd tomography, a giant multilobed abdominal lymphangioma was suspected, which squeezed the intestinal canal and was closely related to the inferior vena cava. The patient underwent an exploratory laparotomy, during which, it was found that the tumor formed extensive adhesions to the transverse colon, small intestine and pelvic wall, and enveloped the abdominal aorta, superior mesenteric artery, inferior mesenteric artery and inferior vena cava to varying degrees. It was diffcult to remove the cyst completely. Postoperative pathology confirmed the diagnosis of retroperitoneal cystic lymphangioma. The patient recovered well after the operation, was eating normally by 5 days postoperatively,and was discharged 10 days postoperatively.The patient was followed up 1 month after postoperatively and no evidence of recurrence was observed. Conclusion In this case, we report a patient with giant retroperitoneal cystic lymphangioma who underwent exploratory laparotomy combined with preoperative abdominal computerd tomography and acute abdominal pain, abdominal distension and dyspnea. Because of the large volume of the tumor and its close relationship with the superior mesenteric artery and other blood vessels, the surgeon used scissors to separate the tumor sharply and removed the whole tumor completely.